PARAMETRIC ANALYSIS ON THE DESIGN OF RF MEMS SERIES SWITCHES - Julio A. Lonac; Gustavo A. Merletti (European Scientific Journal, ESJ, 2015)
A parametric analysis on the design of RF MEMS series switches is performed. The main design variables were identified and a set of RF MEMS series switches were designed, fabricated and measured. The effect of these design variables on the pull-in voltage (Vp) and the RF performance of the switches is studied and simplified equations for design propose are evaluated and corrected on the basis of experimental results.